Theoretical Study of Rotational Spectroscopy of Acetonitrile-d3 in the Ground and Different Excited Vibrational States - Motamedi Masoud; Moradi Parinaz (E-Journal of Chemistry)
The millimeter-wave rotational spectra of the ground and excited vibrational states v8 = 1 and v8 = 2 of the symmetric top molecule CD3CN have been analyzed again. The l = ± 1 in v8 =1, l = 0 and l = ± 2 series in v8 = 2 states have been assigned respectively. The assignment and analysis of the measurements with a least – squares procedure have made it possible to obtain the rotational, quartic and sextic centrifugal distortion constants with more reliable and higher accuracy. Analysis of the v8 = 2 state gave the following rotational parameters: Aζ = 62218.96 MHz and xll = 87527.70 MHz. Investigation in v8 = 2 state indicates that l-resonance is observed for this molecule around k=xℓℓ+(A−B)−2AζAζ−(A−B)≈4 .